Pengembangan LKPD menggunakan model pedagogi reflektif untuk menumbuhkan karakter empati siswa kelas IV SD - Sundari, Niken Dwi; Purnomo, Puji (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2023)
This research was motivated using media, namely LKPD, which does not fully support the learning process and the low empathy character of students. This study aims to develop student worksheets using the reflective pedagogical model to grow the empathy character of natural resource material for grade IV elementary school students and to determine its quality. This study uses the ADDIE-type Research and Development (R&D) method. The object of this study is the LKPD using the reflective pedagogical model to grow an empathetic character. The results of this study show that 1) LKPD uses a reflective pedagogical model to grow the empathy character of natural resource material for grade IV elementary school students was developed using ADDIE, namely Analyze, Design, Develop, Implement, dan Evaluate. 2) The quality of LKPD using the reflective pedagogical model to grow the empathy character of natural resource material for grade IV elementary school students gets an average score of 3,69 with very good criteria. LKPD developed using a reflective pedagogical model can grow empathy character. This is proven by the percentage increase of 37% from the limited trial results. Therefore, LKPD using a reflective pedagogical model to grow empathy character can be widely tested.